Artistic Practices in the Context of the Evolution from Web 1.0 to Web 3.0 - CHIBALASHVILI, Asmati; BEZUHLA, Ruslana; KHARCHENKO, Polina; SEVERYNOVA, Maryna; KORENYUK, Yuriy (Studia Universitatis Babes-Bolyai Musica, 2024)
This article examines the evolution of artists’ interaction with the audience in the context of media culture, linked to the updates of communication mechanisms on the Internet, from the static Web 1.0 to the interactive Web 3.0. The aim of the article is to show the connections between the changes in authorship models and mechanisms of interaction with the audience in artistic practice and the evolutionary development of web technologies. The transformation of contemporary artistic forms is the result of the active influence of digital technologies and the associated collapse of the existing hierarchy between author, performer and audience. The study discusses the strengthening of the interactive component in artistic practices, parallel to the development of Internet technologies from Web 1.0 to the semantic Web 3.0 and analyzes the overlapping of these processes and their mutual influence in the context of post humanist perspectives. It was found that artistic collaborations through collective authorship are a characteristic model of authorship for this phase of Internet development. It was noted that the evolution from Web 2.0 to Web 3.0 opens new possibilities for the creation of multisensory experiences, thanks to the use of VR (Virtual Reality) and AR (Augmented Reality) technologies, which are actively used by artists in artistic practices and works, for example in operas or concerts. In addition, the active development and integration of artificial intelligence technologies in artistic practices has been identified. By analyzing musical projects of different genres and forms, the transformative influence of web culture on contemporary artistic practices becomes clear.